Synthesis of Mesoporous TiO2-Al2O3 Binary Oxides Photocatalyst by Sol-Gel Method Using PEG1000 as Template - Wenjie Zhang; Ruyuan Li; Hongbo He (International Journal of Photoenergy)
The mesoporous TiO2-Al2O3 binary oxides were prepared by sol-gel method using PEG1000 as template. The effects of PEG1000 concentration on the properties and photocatalytic activity of the materials were investigated. The binary oxides were composed of nanocrystallite anatase TiO2 and amorphous Al2O3. The surfaces of the samples prepared with PEG1000 were rough and had many long grooves on the surfaces. When PEG1000 concentration increased from 0 to 0.048 mol/L, the BET specific surface area of the samples changed from 99 to 140 m2·g−1, and the average pore size decreased from 22 to 11 nm. The TiO2-Al2O3 binary oxides prepared at PEG1000 concentration of 0.03 mo/L had the maximum photocatalytic activity and high adsorption capacity. Methyl orange photocatalytic degradation and adsorption rates on 600 mg/l of TiO2-Al2O3 binary oxides were 36.1% and 18.6% after 30 min, respectively. Total removal of the dye was achieved after 3 h of reaction.